Economic nationalism and economic integration : the Austro-Hungarian Empire in the late nineteenth century - Max-Stephan Schulze; Nikolaus Wolf (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper seeks to reconcile two seemingly contradictory strands in the literature on economic development in the late nineteenth century Habsburg Empire - one emphasizing the centrifugal impact of rising intra-empire of nationalism, the other stressing significant improvements in market integration across the empire. We argue that the process of market integration was systematically asymmetric, shaped by intensifying intra-empire nationality conflicts. While grain markets in Austria-Hungary became overall more integrated over time, they also became systematically biased: regions with a similar ethno-linguistic composition of their population came to display significantly smaller price gaps between each other than regions with different compositions. The emergence and persistence of this differential integration cannot be explained by changes in infrastructure and transport costs, simple geographical features or asymmetric integration with neighbouring regions abroad. Instead, differential integration along ethno-linguistic lines was driven by the formation of ethno-linguistic networks. Finally, the analysis shows that the emerging pre-war regional integration patterns shaped by nationalist sentiment effectively anticipated the post-war settlement: the fault lines along which the Habsburg Empire was to break up eventually are evident in the price data about a quarter of a century or so before the outbreak of the First World War.
Keywords: F15; J15; N13; 330; Habsburg Empire; market integration; nationalism; networks; pre-1914 Europe; Wirtschaftsintegration; Nationalismus; Ethnische Gruppe; Business Network; Wirtschaftsgeschichte; Österreich-Ungarn